(untitled) - Watkinson, Anne (London, 2010)
The Essential Guide for New Teaching Assistants provides an introduction for teaching assistants who have recently been inducted, or are going through the process of induction, and are working in schools with children or young people.
Keywords: Teachers’ assistants,Education,Trợ lý giáo viên,Giáo dục; Aims and objectives,Mục đích và mục tiêu; Great Britain,Great Britain,Nước Anh,Nước Anh